TERT—Regulation and Roles in Cancer Formation - Dratwa, Marta; Wysoczańska, Barbara; Łacina, Piotr; Kubik, Tomasz; Bogunia-Kubik, Katarzyna (Frontiers in Immunology, 2020)
Telomerase reverse transcriptase (TERT) is a catalytic subunit of telomerase. Telomerase complex plays a key role in cancer formation by telomere dependent or independent mechanisms. Telomere maintenance mechanisms include complex TERT changes such as gene amplifications, TERT structural variants, TERT promoter germline and somatic mutations, TERT epigenetic changes, and alternative lengthening of telomere. All of them are cancer specific at tissue histotype and at single cell level. TERT expression is regulated in tumors via multiple genetic and epigenetic alterations which affect telomerase activity. Telomerase activity via TERT expression has an impact on telomere length and can be a useful marker in diagnosis and prognosis of various cancers and a new therapy approach. In this review we want to highlight the main roles of TERT in different mechanisms of cancer development and regulation.